Fueling on competition days - Haudum, J. (Journal of Biathlon Coaching, 2024)
In biathlon, where precision meets endurance, the significance of nutrition becomes a pivotal element in optimizing performance. This article focuses on the importance of pre-competition nutrition, emphasizing strategic carbohydrate and hydration intake.